A longitudinal analysis of injury characteristics among elite and amateur tennis players at different tournaments from electronic newspaper reports - Musa R.M.; Hassan I.; Abdullah M.R.; Latiff Azmi M.N.; Abdul Majeed A.P.P.; Abu Osman N.A. (Frontiers Media S.A., 2023)
athlete; electronics; human; incidence; tennis; Athletes; Electronics; Humans; Incidence; Tennis